(untitled) (AYUSHDHARA, 2024)
This study investigates the efficacy of Vaitarana Basti, prepared using an electric mixer to ensure emulsion stability, in managing Amavata symptoms. Aims: To evaluate the efficacy of electric mixer in the preparation of Vaitarana Basti on therapeutic outcomes in patients suffering from Amavata. Settings and Design: The study was conducted as a clinical intervention and followed a single-group, pre-test and post-test design. Ten patients diagnosed with Amavata, presenting with classical joint-specific symptoms, were included. Methods and Material: All ingredients for Vaitarana Basti were mixed using an electric mixer to ensure uniform emulsification. Patients received Yoga Basti (8 Basti) treatment, with assessments carried out both before and after the treatment period. Assessment parameters included joint pain, swelling, stiffness, tenderness, Ayurveda parameters, VAS (Visual Analogue Scale) score, DAS (Disease Activity Score) 28 score, grip strength, and walking time. Statistical analysis used: Wilcoxon signed-rank tests were employed for statistical analysis, comparing pre- and post-treatment scores. P-values less than 0.05 were considered statistically significant, indicating treatment efficacy. Results: The intervention yielded statistically significant improvements in joint-specific symptoms such as pain, swelling, stiffness, and tenderness (p<0.05). VAS and DAS 28 scores also showed significant reductions, and functional indicators like grip strength and walking time improved notably. However, systemic symptoms remained largely unaffected, indicating the localized efficacy of Vaitarana Basti. Conclusions: Vaitarana Basti, prepared with an electric mixer to enhance emulsion uniformity, demonstrated efficacy in relieving joint-specific symptoms of Amavata. While short-term symptom relief was evident, further research is needed to assess long-term effects and the emulsion stability of Basti prepared without traditional emulsifiers.